Sizing Methodology for Hybrid Solar photovoltaic/Hydrogen System using Deterministic Balance Method (DBM)-Case Study in Egypt - Selim, Alaa Emad El Din; El-Shimy, Mohamed; Amer, Ghada (Jurusan Teknik Elektro Universitas Andalas, 2020)
A technical analysis based on modeling, simulation, optimization and verification was conducted for the design of an off-grid hybrid solar PV/hydrogen system. The main objective is to make sizing optimization of the off-grid system to meet the desired electric load of a residential community in a studied region. Additionally, the goal of this study is to have a 100% renewable fraction penetration in the energy mix resulting in a zero percentage of the greenhouse gas emissions and lowering the cost of energy from power systems and verifying the design concept using SAM (System Advisor Model). The effect of meteorological data inputs for the hybrid off-grid system was investigated in Cairo international Airport zone. The distributed power generation in this paper was using solar PV and Fuel Cell energy systems integrated with electrolyzer and hydrogen tank where the main resource for production is the PV modules so that it satisfies the load demand during the peak sun hours and supplying an excess energy to be stored for the later use of fuel cell to supply community load demand of average 4980 kWhr/day.Keywords : Solar PV, Fuel Cell, Hydrogen production, Optimization, off-grid